RELATIONSHIP OF GRANDPARENTING WITH SOCIAL COMPETENCE AND ACADEMIC ACHIEVEMENT OF CHINESE PRIMARY SCHOOL PUPILS - L.P. Hoon; F.D. Hutagalung (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
The purpose of this study was to determine the relationship of grandparenting with social competence and academic achievement of Chinese primary school pupils in Kerian, Perak. This study employed a quantitative correlational design via google forms to obtain data from 130 participants from pupils and teachers. The pupils were required to complete two questionnaires- Grandparent-raising grandchildren Scale, Academic Achievement Questionnaire, while the teachers completed Social Competence Scale-Teacher version (SCT)- measure grandparenting, academic achievement, and social competence scale respectively. Data received was then analyzed using SPSS 25.0 to find out if there is a correlation between the three variables and the level of social competence. Gender and age differences in social competence were also tested. Descriptive statistics were being used to determine the level of social competence. Spearman and Pearson’s correlational tests were run to determine the correlation between variables. An independent sample t-test was being applied to identify any differences that may exist between students of different genders in social competence, whereas the Kruskal-Wallis test was being used to identify age differences in social competence. The findings indicated that the level of social competence among Chinese primary school pupils was high. Positive and significant correlations were found between grandparenting and social competence and academic achievement. However, there were no significant gender and age differences in social competence. Overall, current findings emphasized the need to consider the role of grandparenting in association with social competence and academic achievement, since it could create long-lasting impact in a child’s lives.